A plasticidade humana e as ficções barrocas: um estudo de Las Repeticiones de Silvina Ocampo - Matar, Amanda Queiróz (2022)
In this dissertation, selected short stories from the posthumously published work Las Repeticiones by the Argentine writer Silvina Ocampo were analyzed. The analysis was made based on the theories of the secular humanism, considering the influences of Spanish humanism and the Siglo de Oro, also bearing in mind the concept of plastic capacity achievable through the game of fiction, evidenced not only in the work itself but also in Silvina's attitude towards life. The analysis of the short stories also has the critical and theoretical support of what Carlos Gamerro, Argentine theorist and novelist, presents about baroque writings and fictions, in other words the game of fiction that removes borders between the imaginary and the references of reality. For Gamerro, Ocampo does not have a baroque style in terms of language, according to the famous classification of baroque as a play on words, but rather at the level of ideas. The Argentine critic attributes the baroque character of fiction to Cervantes and Calderón de la Barca. Thus he defends that Hispanic-American writers commonly known as fantastic – Borges, Bioy Casares, Cortázar, Silvina Ocampo, – are in fact fiction authors who build a game of narrative structures, characters and the universal real referential. Nevertheless, it is also intended to demonstrate how these issues prevail from the analysis of the short stories selected for the work.